2015
DOI: 10.7150/thno.11974
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmonic Gold Nanostar Theranostic Probe for In Vivo Tumor Imaging and Photothermal Therapy

Abstract: Nanomedicine has attracted increasing attention in recent years, because it offers great promise to provide personalized diagnostics and therapy with improved treatment efficacy and specificity. In this study, we developed a gold nanostar (GNS) probe for multi-modality theranostics including surface-enhanced Raman scattering (SERS) detection, x-ray computed tomography (CT), two-photon luminescence (TPL) imaging, and photothermal therapy (PTT). We performed radiolabeling, as well as CT and optical imaging, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
214
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(223 citation statements)
references
References 64 publications
7
214
0
2
Order By: Relevance
“…13,37 Thus, gold nanostars are unique materials with an intense surface plasmon band that affords absorption in the near-infrared region. [21][22][23][24][25][26] with MTX-nanostars during 48 hours of incubation using the Perkin Elmer Spotlight 400 system for the FTIR and the LabRAM HR Evolution spectrometer for the SERS maps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,37 Thus, gold nanostars are unique materials with an intense surface plasmon band that affords absorption in the near-infrared region. [21][22][23][24][25][26] with MTX-nanostars during 48 hours of incubation using the Perkin Elmer Spotlight 400 system for the FTIR and the LabRAM HR Evolution spectrometer for the SERS maps.…”
Section: Resultsmentioning
confidence: 99%
“…16 Gold nanostars, star-shaped gold nanoparticles, have exceptional optical properties. [17][18][19][20] They display two surface plasmon bands consistent to the transverse and longitudinal surface plasmon bands in the visible (520 nm) and the near-infrared regions, respectively 15 Thus, gold nanostars are special materials with an intense surface plasmon band that affords absorption, fluorescence [21][22][23] and light scattering 24,25 in the near-infrared region, inducing two-photon luminescence phenomena. 26 Hexadecyltrimethylammonium bromide (CTAB) is a common material for gold nanostar synthesis.…”
mentioning
confidence: 99%
“…Within the large spectrum of gold nanostructures, numerous reports describe the intrinsic luminescence properties of such systems [106][107][108][109][110][111][112][113][114]. This interesting feature is a great alternative with regard to light scattering measurements [7,115], especially for biological or clinical applications with an easier detection and localization of these particles.…”
Section: Photoluminescence Of Individual Naked Plasmonic Nanoparticlesmentioning
confidence: 99%
“…GNS are exceptional light 'nano-enhancers' that have led to a wide range of chemical, biological and medical (both diagnostic and therapeutic) applications. For example, GNS exhibit intense surface-enhanced Raman scattering and two-photon luminescence and therefore provide an exceptional platform for nucleic acid biomarker detection [13,17], stem cell tracking [25,26] and tumor bioimaging [18,19].…”
Section: Plasmonic Nano-enhancers Of Lightmentioning
confidence: 99%
“…A special type of metallic nanoparticles, called 'plasmonic' nanoparticles, has received great interest because they exhibit enhanced optical and electromagnetic properties. Our fundamental studies of various plasmonic structures [8][9][10] and applied development of plasmonic nanoplatforms have led to a wide variety of applications ranging from chemical sensing [10][11][12] to cancer diagnostics [13][14][15][16][17] and therapy using nanoparticle-mediated photothermal treatment [15,[18][19][20]. Recently, we demonstrated that the use of plasmonic gold nanostars (GNS) in combination with immunotherapy -a treatment we referred to as Synergistic Immuno Photothermal Nanotherapy (SYMPHONY) -can dramatically enhance the efficacy of immunotherapy.…”
mentioning
confidence: 99%